Effective teaching strategies lessons from research and practice - Killen, Roy 1947-; O'Toole, Mitch (Cengage Learning Australia, 2022)
Effective Teaching Strategies: Lessons from Research and Practice provides a practical overview of nine common teaching strategies used in all levels of education and training from early childhood through to higher education. Initial chapters discuss the range of teaching strategies, the Australian Curriculum framework and introduce the key principles of quality teaching and learning. These ideas are then applied through chapters devoted to different teaching strategies: direct instruction, discussion, small-group work, cooperative learning, problem solving, inquiry, role-play, case study and student writing. This structure, and balance between theory and very practical strategies, makes this market-leading text a valuable resource for students to use across multiple courses – especially in their professional placement – as well as in their future classrooms. Instructor resources include NEW instructor guide and updated PowerPoints and lesson planning documents